2012
DOI: 10.4038/sljastats.v12i0.4967
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Lung Function and Hypertension among Rural Canadians using Fractional Polynomials

Abstract: Studies have shown that persons with lower pulmonary function have a higher risk for developing cardiovascular diseases including hypertension. The objectives of this paper are to examine: (i) the relationship between lung function and hypertension; and (ii) the correct functional forms of the continuous predictors of hypertension using fractional polynomials. This analysis was based on data from a cross-sectional community study of 1,834 adult subjects aged 18-79 years conducted in 2003 in Humboldt, Saskatche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…14,36 Cohort studies have shown that the reduced lung function parameters are strong, inverse predictors for the future development of hypertension in the able-bodied population. 14,16,17,19,22,44,45 In addition, it has been reported that, although the changes in lung function were predictive of incident hypertension, changes in blood pressure were not predictive of loss of lung function. 19 Furthermore, it has been found that the incidence of CVD and death associated with hypertension is increased in the presence of reduced lung function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,36 Cohort studies have shown that the reduced lung function parameters are strong, inverse predictors for the future development of hypertension in the able-bodied population. 14,16,17,19,22,44,45 In addition, it has been reported that, although the changes in lung function were predictive of incident hypertension, changes in blood pressure were not predictive of loss of lung function. 19 Furthermore, it has been found that the incidence of CVD and death associated with hypertension is increased in the presence of reduced lung function.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,12,13 In the general population, there is strong evidence that people with lower lung function measures (in the absence of overt respiratory symptoms or disease) have a higher risk for developing DM and hypertension. 4,[14][15][16][17][18][19][20][21][22] Lung function predicts the development of insulin resistance or DM, 14,15,20,21 and it is also a useful predictor of subsequent development of hypertension in able-bodied people. [16][17][18]22,23 Although CVD is a major cause for mortality in the SCI population, it is not yet known whether the same association between reduced lung function and future development of DM and hypertension exists in people with SCI.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we only used data from type 2 survey (n ¼ 13 855) participants who underwent several physiological measurements, including lung function tests. We excluded those who withdrew from the study by 13 July 2021, failed to return the self-reported questionnaire, did not undergo physiological measurements, or had missing data regarding lung function, SBP, DBP, plasma glucose, glycated hemoglobin A1c (HbA1c), total cholesterol (TC), triglyceride, high-density lipoprotein cholesterol (HDL-C), urinary creatinine, estimated urinary 24-h sodium excretion, estimated urinary 24 h potassium excretion and white blood cell (WBC) count (n ¼ 1332). Finally, data from 12 523 participants (3728 men and 8795 women) were analyzed.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Hypertension is a well known leading risk factor for cardiovascular disease [5]. Therefore, several studies have examined the association between lung function and hypertension [6][7][8][9][10][11][12][13][14], and these studies have shown that lung function is inversely associated with blood pressure (BP) and hypertension [6][7][8][9][10][11][12][13]. However, only a few studies have reported an association between lung function and hypertension among never-smokers [7,8], although smoking is closely associated with reduced lung function and is positively associated with BP [15][16][17][18].…”
mentioning
confidence: 99%